ANALISIS KEPUASAN PELANGGAN PADA LAYANAN TRAVELOKA - Luthfiyah Febriyanti (2020)
The research is a quantitative study the factors that increase customer satisfaction on the factors of trust, sales promotion and service quality. The population in this research is Traveloka service users. The number of samples taken was 75 respondents with a non-probability sampling technique specifically purposive sampling. Data collection in this study through the collection of questionnaires using Google forms. The analysis technique used is the PLS (Partial Least Square) analysis method with SmartPLS software version 3.2. The results of this study indicate (1) of 0.648 positive and significant trust in customer satisfaction, (2) of 0.327 positive and significant sales promotion of customer satisfaction. (3) 0.546 positive and significant quality of service to customer satisfaction. With R-Square Adjusted generated at 72.5%. Keywords: Trust, Sales Promotion, Service Quality, Customer Satisfaction